2011
DOI: 10.1007/s10597-011-9373-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mental Healthiness Aging Initiative: Community Program to Promote Awareness About Mental Health and Aging Issues

Abstract: The objective of this study is to evaluate the Mental Healthiness Aging Initiative, designed to promote community awareness and knowledge about mental health and aging issues. This study occurred during 2007-2009 in 67 of 120 counties in Kentucky. A rural region (11 counties) received the intervention, consisting of focus groups, Extension Agent training, and television-based social marketing campaign. Partial-intervention counties (29 counties) received only the television-based social marketing campaign. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Implementing this project was considered a salient step toward decreasing mental health-related disadvantages experienced by older adults, particularly those residing in rural communities (Glasgow et al, 2004;Mainous and Kohrs, 1995). Through the iterative development and execution of the program, components of community-participation and empowerment were embraced during all phases of the project (See Kruger et al, 2011a;Kruger et al, 2011b;Zanjani et al, 2011).…”
Section: The Study: Description and Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementing this project was considered a salient step toward decreasing mental health-related disadvantages experienced by older adults, particularly those residing in rural communities (Glasgow et al, 2004;Mainous and Kohrs, 1995). Through the iterative development and execution of the program, components of community-participation and empowerment were embraced during all phases of the project (See Kruger et al, 2011a;Kruger et al, 2011b;Zanjani et al, 2011).…”
Section: The Study: Description and Overviewmentioning
confidence: 99%
“…The control counties (27 counties) received no intervention activities. The findings demonstrated that community interventions focusing on mental health can be effective within rural regions, as evidenced by an increased level of knowledge, about mental health and aging in intervention counties, assessed through a telephone survey (conducted by an independent contractor unaffiliated with the MHAI project) of 774 randomly selected individuals across the region (see Zanjani et al, 2011).…”
Section: The Study: Description and Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health problems afflict people irrespective of their age, gender, socioeconomic status, educational level, profession, marital status, resident status, religion affiliation, ethnicity and creed. Therefore, MH studies assessed MH awareness not only of public but also mental health professionals [18], other health practitioners [19], college students [20,21], indigenous people [22], refugees and homeless people [23] and also people with diverse individual mental disorders [24,25] including schizophrenia [26,27], depression [28][29][30], anxiety disorders [31,32], dementia [33,34], alcohol and other drug abuse, and technology addictions [35,36], personality disorders [37], child and adolescents disorders including suicide and child abuse/neglect [38][39][40], physical comorbidities [41,42], mental health organizations and their impact on MHL [43,44] and intellectual disabilities with MH problems [45]. Furthermore, mental health awareness surveys and implementation of training programs and campaigns have been carried out in several settings targeting different age groups affected by MH problems such as schools [46].…”
Section: Introductionmentioning
confidence: 99%
“…A focus on synthesis and integration types of reminiscence is known to promote successful aging (Wong & Watt, 1991). The development of MB builds on findings from earlier research and the Mental Healthiness Aging Initiative (MHAI), a program created to raise awareness and knowledge in rural areas about the mental health of older adults through collaborations with the University of Kentucky’s Cooperative Extension Service (Kruger, Murray, Zanjani, 2011a, 2011b; Zanjani, Kruger, & Murray, 2011). Through MHAI, specific themes related to the management of mental health and aging were identified and incorporated into MB, including the importance of emotional health, the ability to remain active and engaged through old age, the importance of intergenerational activities, and most important being the value of sharing one’s life story.…”
Section: Introductionmentioning
confidence: 99%